2016
DOI: 10.18632/oncotarget.11003
|View full text |Cite
|
Sign up to set email alerts
|

miR-513a-5p regulates radiosensitivity of osteosarcoma by targeting human apurinic/apyrimidinic endonuclease

Abstract: Radiotherapy in osteosarcoma patients is problematic due to radioresistance; therefore, understanding the mechanism of radioresistance is integral to providing effective radiotherapeutic regimens for osteosarcoma. We now report the activity of an miRNA, miR-513a-5p, in stimulating radiosensitivity of osteosarcoma cells in vitro and in vivo. MiR-513a-5p expression is decreased in osteosarcoma tissue from patients and cultured osteosarcoma cell lines. However, exogenous re-expression of this miRNA in osteosarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
(28 reference statements)
1
24
0
Order By: Relevance
“…Radiotherapy has been utilized for malignant tumor for decades. Radiotherapy is applied to a small proportion of OS patients such as inoperable OS and painful bone metastasis [ 5 ]. Local control could be achieved by radiotherapy which is used as an adjuvant method in OS patients receiving intralesional resection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy has been utilized for malignant tumor for decades. Radiotherapy is applied to a small proportion of OS patients such as inoperable OS and painful bone metastasis [ 5 ]. Local control could be achieved by radiotherapy which is used as an adjuvant method in OS patients receiving intralesional resection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the brown module, which was mainly involved in DNA replication and mitotic nuclear division and was observed to be positively correlated with the trait of osteosarcoma tissue, previous studies have revealed that genes involved with DNA replication and DNA damage were associated with radiosensitivity of osteosarcoma [13], as well as drug sensitivity [14]. Our results indicated that genes in the brown module might be related with carcinogenesis of osteosarcoma and might provide insights for exploring drug targets for the treatment of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, decreasing Ape1 expression levels with small interfering RNA (siRNA) was able to sensitize osteosarcoma xenografts to the antiangiogenic endostatin [370]. The miRNA miR-513a-5p has been found to supress APE1 expression in osteosarcoma cell lines including HOS and U2-OS, rendering them radiosensitive [371]. In addition, miR-765 was found to sensitize osteosarcoma cells lines (HOS and 9901) and tumour xenografts to cisplatin due to downregulation of Ape1 [372], making targeting APE1 through miRNA a treatment option for resistant osteosarcoma.…”
Section: Alterations In Dna Repair Pathwaysmentioning
confidence: 91%